Community Empowerment through the Waste Bank Program by CSR of PT Pertamina Patra Niaga Bitumen Plant Gresik - Jahiroh, Luluk Atun; Wildan Andaru (Prospect Publishing, 2025)
The waste management issue in Padeg Village, Gresik Regency, has become increasingly complex due to the suboptimal management of the Temporary Disposal Site (TPS). The accumulated waste is often burned in the open, directly impacting both the environment and the health of nearby residents. PT Pertamina Patra Niaga – Bitumen Plant Gresik has taken part in addressing this issue through its Corporate Social Responsibility (CSR) program by supporting the establishment and development of the Pandean Pas Waste Bank. This study aims to describe the implementation of PT Pertamina Patra – Niaga Bitumen Plant Gresik’s CSR program in community empowerment through public participation in the Pandean Pas Waste Bank Program. The research methid employed is descriptive, qualitative, with data collected through observation, interviews, and documentation studies. The results indicate that the CSR program has successfully increased active community participation at every stage of the empowerment process. The Pandean Pas Waste Bank program has effectively reduced household waste generation, produced organic compost, and contributed to environmental sustainability. The company’s CSR initiative has not only improved waste management practices but also enhanced the capacity, participation, and independence of the Padeg Village community in preserving environmental sustainability.